1990
DOI: 10.1161/01.hyp.15.2_suppl.i59
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous fenoldopam versus sodium nitroprusside in patients with severe hypertension.

Abstract: In an open-label study, we compared the efficacy and safety of intravenous infusion of fenoldopam mesylate with that of sodium nitroprusside in patients with severe hypertension or in hypertensive crisis. Both antihypertensive medications were infused at a maximal dose increment of 0.2 microgram/kg/min (fenoldopam) and 1 microgram/kg/min (nitroprusside), with a maximal infusion rate of 1.5 micrograms/kg/min fenoldopam mesylate or 8 micrograms/kg/min sodium nitroprusside. Once the desired reduction in diastolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 7 publications
0
25
0
2
Order By: Relevance
“…[24][25][26][27][28][29][30][31][32][33][34][35] Other trials included patients without explicitly stating whether patients had acute end-organ damage or not (7 trials). [36][37][38][39][40][41][42] Some trials included non-randomized participants in the trial's results (1 trial). 43 One trial did not report any of the outcomes of interest (1 trial).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27][28][29][30][31][32][33][34][35] Other trials included patients without explicitly stating whether patients had acute end-organ damage or not (7 trials). [36][37][38][39][40][41][42] Some trials included non-randomized participants in the trial's results (1 trial). 43 One trial did not report any of the outcomes of interest (1 trial).…”
Section: Resultsmentioning
confidence: 99%
“…In 19 of the excluded trials [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] it was not possible to determine how many patients had acute endorgan damage or merely had elevation of blood pressure. We believe that it would be misleading to include these trials in this review as the impact of antihypertensive drugs is potentially different.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nitroprusside poses a concern about thiocyanate toxicity. In a single study of 9 patients, nitroprusside is reported to have increased plasma thiocyanate concentration in 2 patients, but there were no signs of toxicity [78].…”
Section: Pharmacologic Evidence For the Role Of The D1-like Receptor mentioning
confidence: 94%
“…Chronic administration of ecopipam increases blood pressure in humans [78]. Chronic D1-like receptor blockade in rodents also increases blood pressure [79].…”
Section: Pharmacologic Evidence For the Role Of The D1-like Receptor mentioning
confidence: 99%
“…It produces no toxic metabolites and has been shown to be as effective in blood pressure reduction as nitroprusside. 28,29 In the special case of scleroderma renal crisis, angiotensin-converting enzyme inhibitors (eg, captopril and enalapril) are first-line agents for effect management. 30 …”
Section: Aortic Dissectionmentioning
confidence: 99%